Human Herpes Virus 6 and Encephalitis in Children - Elda Skenderi; Gjeorgjina Kuli-Lito; Admir Sulovari; Nilsa Shahini; Griselda Toci; Ada Pema (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
Abstract Human herpesvirus 6 was the sixth herpesvirus discovered, it is a beta-herpesvirus and is ubiquitous in nature. Primary infection with HHV-6 occurs within the first 2 years of life and is usually associated with an undifferentiated febrile illness, although a subset of children exhibit the classic manifestations of roseola infantum. After primary infection, the virus replicates in salivary glands and is shed in saliva, the recognized route of transmission. It remains latent in lymphocytes and monocytes and persists at low levels in cells and tissues. HHV-6 is probably the most neurotropic virus known, it has been implicated as a cause of encephalitis in transplant recipients but occasionally is reported as a cause of meningitis and encephalitis in immunocompetent individuals. We present the case of a 21-month old infant diagnosed with HHV-6 encephalitis.